The role of Si at a lower level on the mechanical properties of Al-based automotive alloys - Khan A.A.; Hossain Al-K.; Kaiser M.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Resistance spot welding studies at varying current with an 8 mm electrode on steel grades DP980, DP690, TRIP980, and TRIP780, established that peak strength with sound weld could be achieved at a current range of 9 to 10 kA, where the nugget diameter was between 6.9 and 7.5 mm. The joint efficiency, measured as hardening ratio was highest in TRIP690 at 2.22 and for higher strength grade it was between 1.37 and 1.51. The softening ratio in the HAZ associated with tempering of preexisting martensite, was 0.86 to 0.9. Higher fusion strength was associated with alloying content that increased resistance that increased weld pool fusion that further enhanced the nugget diameter and hence the strength. The TRIP steel at high cooling rate showed martensite and retained austenite and the DP steel showed martensite content in higher grade and dispersed ferrite with martensite in the lower DP grade. The Tensile shear strength was lowest (16kN) for DP780, while for other grades it was between 20 and 22 kN. The strength enhancement in TRIP steel was due to higher weld diameter at higher current, where partial pull out failure mode was observed. At lower current, the interfacial pull out failure mode was observed with poor fusion and at high currents partial pull out at HAZ was observed. The Coach peel strength was highest at 3.2 kN for DP780, 2.2 kN for DP980, 2 kN for TRIP 690 and 1.7kN for TRIP 980 which followed the trend in TSS. The observed failure may be attributed to the high fusion strength in TRIP steel due to sound nugget and a microstructure of martensite with retained austenite. The lower strength with DP steels was attributed to low alloyed lath martensite in DP 980 and the lower grade DP780 was softer which was associated with ferrite dispersion in martensite. At very high currents, the fusion was good but there was a pull out at HAZ due to the softening associated with the tempering of preexisting martensite that influenced the failure at HAZ failure mode.